Optimizing the date of transplanting to increase seed yield and quality in davana (Artemisia pallens Wall.ex.D.C.) - K Vanangamudi, K Rajamani, M Jayanthi, A Vijayakumar, (Journal of Spices and Aromatic Crops, 2014)
A field experiment was conducted to study the effect of date of transplanting on growth, yield and seed quality attributes of davana. The experiment was laid out with five different dates of transplanting viz., October 15th, November 1st, November 15th, December 1st and December 15th with the spacing of 15 cm × 7.5 cm. The results revealed that the seedlings transplanted on 15th November recorded the maximum number of branches plant-1 (26), herbage yield plot-1 (1064.39 g), seed yield plant-1 (9.01 g), seed yield plot-1 (112.66 g), resultant seed germination (64%) and vigour index (168) whereas the seedlings transplanted on December 15th recorded the minimum number of branches plant-1 (20), herbage yield plot-1 (799.62 g), seed yield plant-1 (6.33 g), seed yield plot-1 (79.08 g) and the seedlings transplanted on October 15th recorded 61% seed germination and vigour index of 145.